Multi-objective path planning for unrestricted mobile - Feng Guo; Hongrui Wang; Yantao Tian (2009 IEEE International Conference on Automation and Logistics, 2009)
Problem of multi-objective path planning is investigated in this paper for the ball and plate system. The purpose of multi-objective path planning is to obtain the safe and shortest path for the ball to track. Workspace is represented by distance map and hazard map. Weights for multi-objectives are calculated by entropy method for each grid node. Dijkstra algorithm is employed to solve the multi-objective path planning problem finally. As illustrated by simulation results, the path obtained by multi-objective method proposed in this paper is much safer compared with single-objective A* algorithm.